2011
DOI: 10.1063/1.3605510
|View full text |Cite
|
Sign up to set email alerts
|

Structural origin underlying poor glass forming ability of Al metallic glass

Abstract: We performed molecular dynamics simulations to study the glass formation and local atomic structure of rapidly quenched Al. Both potential energy and structural parameters indicate that the glass transition temperature of amorphous Al is as low as 300 K, which may lead to the poor thermal stability of the amorphous Al as it is prone to crystallize even at room temperature. Voronoi polyhedra analysis reveals that the most popular polyhedron is the deformed body-centered cubic (bcc) cluster characterized by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…[10][11][12] Recently, Li et al proposed that abundant deformed-bcc clusters existing in the amorphous structure could be the reason for the poor GFA of the amorphous Al. 13 However, for Al 75 Co 25 MG with better GFA, the most popular polyhedron is full icosahedron with Voronoi index h0,0,12,0i, which is always predominant in the BMGs formers with excellent GFA. 14 The other route is based upon the experimental analyses using synchrotron radiation x-ray diffraction (XRD) 15 and fluctuation electron microscopy 16 to provide key information of short range order (SRO) and medium range order (MRO).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Recently, Li et al proposed that abundant deformed-bcc clusters existing in the amorphous structure could be the reason for the poor GFA of the amorphous Al. 13 However, for Al 75 Co 25 MG with better GFA, the most popular polyhedron is full icosahedron with Voronoi index h0,0,12,0i, which is always predominant in the BMGs formers with excellent GFA. 14 The other route is based upon the experimental analyses using synchrotron radiation x-ray diffraction (XRD) 15 and fluctuation electron microscopy 16 to provide key information of short range order (SRO) and medium range order (MRO).…”
Section: Introductionmentioning
confidence: 99%
“…The Wendt–Abraham parameter emphasizes the local character of g(r) , permitting a direct comparison between different structures and leading to a better estimate of the glass transition temperature ( T g ). [ 36,37 ]…”
Section: Resultsmentioning
confidence: 99%
“…At present, the study on molecular-dynamics simulations has shown that the Al-based amorphous alloys had a low T g and contained a large amount of deformed body-centered cubic (bcc) short-range orders, while the icosahedron is always predominant in the amorphous matrix [41]. Moreover, these deformed-bcc short-range orders could make up medium-range orders via some linkages, such as edge-, face-, intercrossed-shared atoms, which were believed to more easily transform into the fcc nanocrystals, compared with the icosahedral clusters due to the symmetrical similarity between bcc and fcc structures.…”
Section: Alloys Systemmentioning
confidence: 99%